Research on the Practice Path of Integrating Red Gene into College Students' Ideological and Political Education - Wang, Shenggang; Yu, Hengguang (Pacific International Journal, 2024)
Since its establishment, the Communist Party of China (CPC) has United and led the people of China to overcome difficulties and challenges, made great achievements and won great victories. In this process, the Communist Party of China (CPC) people have formed a unique spiritual core "Red Gene". The red gene is the inheritance of China's revolutionary spirit, and it is also the precious wealth of the Chinese nation, inspiring Chinese descendants to keep moving forward. Integrating the red gene into the ideological and political education of college students is an important guarantee for implementing the fundamental task of cultivating people by virtue and is also the need for developing Socialism with Chinese characteristics.